Nano-microplastic and agro-ecosystems: a mini-review - Verma, Krishan K.; Song, Xiu-Peng; Xu, Lin; Huang, Hai-Rong; Liang, Qiang; Seth, Chandra Shekhar; Li, Yang-Rui (Frontiers in Plant Science, 2023)
Plastics' unavoidable and rampant usage causes their trash to be extensively dispersed in the atmosphere and land due to its numerous characteristics. Because of extensive plastic usage and increased manufacturing, there is insufficient recycling and a large accumulation of microplastics (MPs) in the environment. In addition to their wide availability in the soil and atmosphere, micro- and nanoplastics are becoming contaminants worldwide. Agro-ecosystem functioning and plant development are being negatively impacted in several ways by the contamination of the environment and farmland soils with MPs (<5 mm) and nanoplastics (<1 µm). The contributions of some recyclable organic waste and plastic film mulching and plastic particle deposition in agroecosystems may be substantial; therefore, it is crucial to understand any potentially hazardous or undesirable impacts of these pollutants on agroecosystems. The dissolution of bioplastics into micro- and nano-particles (MBPs and NBPs) has not been considered in recent studies, which focus primarily on agro-ecosystems. It is essential to properly understand the distribution, concentration, fate, and main source of MPs, NPS, MBPs, and NBPs in agroecosystems. Based on the limited findings, understanding the knowledge gap of environmental impact from micro and nanoplastic in farming systems does not equate to the absence of such evidence. It reveals the considerations for addressing the gaps to effectively protect global food safety and security in the near future.